2001
DOI: 10.1016/s0092-8674(01)00298-7
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Rho-Associated Kinase (Drok) Links Frizzled-Mediated Planar Cell Polarity Signaling to the Actin Cytoskeleton

Abstract: Frizzled (Fz) and Dishevelled (Dsh) are components of an evolutionarily conserved signaling pathway that regulates planar cell polarity. How this signaling pathway directs asymmetric cytoskeletal reorganization and polarized cell morphology remains unknown. Here, we show that Drosophila Rho-associated kinase (Drok) works downstream of Fz/Dsh to mediate a branch of the planar polarity pathway involved in ommatidial rotation in the eye and in restricting actin bundle formation to a single site in developing wing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
551
1
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(579 citation statements)
references
References 49 publications
22
551
1
5
Order By: Relevance
“…Rho-GTPases have also been implicated in the morphogenesis of tissues in developing multicellular organisms. In Drosophila, the Rho-Rho-kinase pathway is involved in a number of morphogenetic-related PCP events, such as cellular rearrangement at germ band elongation and establishment of orientation of ommatidia and hairs (Winter et al, 2001;Bertet et al, 2004); and Rho, Rac, and Cdc42 regulate cytoskeletal reorganization of dorsal closure (Harden et al, 1999). In mice, the Rho-Rho-kinase pathway is involved in eyelid formation (Shimizu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Rho-GTPases have also been implicated in the morphogenesis of tissues in developing multicellular organisms. In Drosophila, the Rho-Rho-kinase pathway is involved in a number of morphogenetic-related PCP events, such as cellular rearrangement at germ band elongation and establishment of orientation of ommatidia and hairs (Winter et al, 2001;Bertet et al, 2004); and Rho, Rac, and Cdc42 regulate cytoskeletal reorganization of dorsal closure (Harden et al, 1999). In mice, the Rho-Rho-kinase pathway is involved in eyelid formation (Shimizu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila embryos, it also appears that Rok is the primary activating kinase of Sqh (myosin II regulatory light chain), and that Sqh is the primary target of Rok phosphorylation (Winter et al, 2001). Rok also phosphorylates and inactivates myosin light chain phosphatase, further promoting the phosphorylated and active state of Sqh (Mitonaka et al, 2007).…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…Rho-associated kinase (ROK) regulates cytoskeletal aspects of planar polarity in Drosophila (Winter et al, 2001) and CE movements in zebrafish . Xenopus ROK␣ (xROK␣) interacts with a Xenopus insulin receptor substrate-1 (xIRS-1) and acts as a potentiator of insulin-induced mitogen-activated protein kinase activation in Xenopus oocytes (Farah et al, 1998;Ohan et al, 1999).…”
Section: Rok␣ Is Involved In Xenopus Ce Movements Without Affecting Gmentioning
confidence: 99%
“…ROK regulates the cytoskeletal aspects of planar polarity in Drosophila (Winter et al, 2001) and CE movements in zebrafish . Data from the present study showed that xROK␣ regulates, as a target of XRhoA, CE movements in whole embryos and Keller explants without affecting gene expression.…”
Section: Rok␣ Regulates Xenopus Ce Movements By Means Of Rhoa But Nomentioning
confidence: 99%
See 1 more Smart Citation